EFFECT OF DIATOMITE AND POULTRY MANURE ON THE PHYSICOCHEMICAL PROPERTIES OF GRAY FOREST SOILS AND CROP PRODUCTIVITY - K.Y. Kovalsky; А.N. Arefiev; Е.N. Kuzin; Е.Е. Kuzina (Volga Region Farmland, 2022)
The aim of the research was to study the effect of diatomite norms from 4 to 10 t/ha and their combinations with poultry manure on the physical and chemical properties of gray forest soils and crop productivity. To fulfill the goal, field experiments were conducted in the Vadinsk-Mokshan agro-soil district of Penza region in the period from 2019 to 2021. The studies determined that the most significant effect on increasing the capacity of cation exchange, the amount of exchangeable bases, decrease in the concentration of hydrogen ions in the soil absorbing complex had the effect and aftereffect of diatomite in the complex with poultry manure. It was found that the highest effect on the productivity of corn, spring wheat and annual grasses was the use of diatomite in combination with poultry manure. At the same time, the efficiency of corn productivity increased by 47.8-59.6%; the productivity of spring wheat increased by 26.8-35.4%; the productivity of vetch-oats increased by 22.8-36.6%. The total productivity of crops in the grain and fallow crops rotation ranged from 13.03 to 14.11 t/ha g.u. exceeding the control by 34.75-45.92 %.